Improving Access to Patient Services at Pharmaceutical Health Services Unit through Health Service Promotion Programs - Wulandari, Cyntia; Zunnita, Oktaviana; Setiani, Lusi Agus (Jurnal Pengabdian Masyarakat Inovatif, 2024)
Health promotion is the dissemination of health messages or a form of health education and improving health for the community. Health promotion activities, one of which is free health services to the community, can increase people's enthusiasm to come to health facilities. The purpose of this activity is to increase access to health services from Universitas Pakuan human resources to Pakuan Farma Pharmacy. Activities are carried out with the basic health check method of degenerative diseases recording the results of examinations and providing education and referrals for health therapies and ways of recommending healthy living. Promotion of health service facilities Pakuan Farma Pharmacy with the distribution of pharmacy brochures and multivitamins and activity participants can also get a free consultation from doctor Ghrena from the Health Unit of Faculty in Universitas Pakuan to get therapy and the use of appropriate drugs and drugs on prescriptions can be obtained from Pakuan Farma Pharmacy. The number of participants who participated in the activity was 91 participants with the average results of checking blood sugar levels 115 mg / dL, Cholesterol 189.67 mg / dL, Uric Acid (Men) 5.8 mg / dL, Uric Acid (Women) 5.8 mg / dL, Blood Pressure 136 / 84 mmHg and Average Body Weight 65 Kg. The average results of health checks show that the health service program has had a positive impact on knowing health conditions or first screening for Universitas Pakuan human resources who participated in this activity.  Although most parameters are within normal ranges, continued efforts need to be made to prevent and manage certain health risk factors, especially in blood pressure. With a deep understanding of this condition, it is hoped that health service programs can continue to be improved to support the overall welfare of Universitas Pakuan human resources.